Անգլերեն հատուկ նպատակների համար (ESP). բնորոշ գծերը, նպատակները և տեսակետները: Զուգահեռներ ESP-ի և ընդհանուր անգլերենի միջև - Հասմիկ Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
Роль ESP курса обучения английского языка растет во всем мире благодаря возрастающим требованиям более профессионального лингвистического подхода к той или иной сфере науки или профессиональной деятельности. Настоящий курс обучения английского языка сравнительно молод в Армении и он все еще развивается. Тем не менее обсуждения, касающиеся формулировки, целей и задач ESP курса, все еще продолжаются и разные специалисты предлагают различные мнения относительно его формулировки. Для эффективной организации курса важно выделить первостепенные цели, задачи и требования учащихся к изучению английского языка. В статье также рассматриваются эффективные пути для раскрытия лингвистических нужд и требований учащихся. Приводятся параллели между курсами ESP и общего английского.The role of ESP course is growing worldwide due to the increasing demand for more professional linguistic approach to this or that area of science or professional activity. The given English learning course is relatively young in Armenia and is still developing. However, the discussions around the definitions, goals and tasks of ESP course still continue and different specialists offer a variety of views and characterizations regarding its definition. In order to organize the course effectively it’s important to reveal learners’ primary goals, tasks and requirements in studying English. The article also considers effective ways to discover learners’ linguistic needs and requirements. Parallels are drawn between the ESP and General English courses.
Keywords: Education; Theory and practice of education; Language and Literature